The Empowerment Effectiveness through the Family of Hope Program (PKH) - Adibowo, Rino; Dewi, Eka Nuryanti; Faris, Gilang Muhamad; Nurdamaiati, Dewi; Fahlevi, Mochamad Daffa; Hartanto, Gaya Prakasa; Mukarom, Ahmad Syahrul (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The Family of Hope Program (PKH) is a cash transfer program for very poor Households to improve the quality of the poor's resources through empowering mothers and encouraging their children to stay in school. PKH is a Ministry program, the main actors are from the Social Service, then assisted by Central Bureau of Statistics, the Education Office and the Health Office. The problems that exist in the Family of Hope Program in Majalengka, such as the inaccurate targeting, lack of communication between officials and the community, inadequate facilities for officials and the community. The research method used is descriptive method with a qualitative approach. Data collection techniques used are observation, literature study and interviews. The research informants were determined using the purposive method, namely the Family of Hope Program apparatus and beneficiary communities in Majalengka. The results of the study showed that the input in the Family of Hope Program still contained several obstacles which resulted in not creating the effectiveness of the Family of Hope Program in Majalengka, the inadequate facilities owned by the apparatus and the community were one of the causes. The production process, seen from communication, has several obstacles, one of which is that some people do not know about this program because they do not use social media, this has resulted in the ineffectiveness of the Family of Hope Program in Majalengka. Physical products in the form of cards can be used properly by the community. Productivity in Family of Hope Program seen from the education of the apparatus, motivation and income, this can be said to have been effective in the Family of Hope Program.